Cost-Effectiveness of Antibiotic-Eluting Envelope for Prevention of Cardiac Implantable Electronic Device Infections in Heart Failure. Issue 3 (2nd February 2022) - Modi, Ronuk M.; Liu, Chia-Liang; Isaza, Nicolas; Raber, Inbar; Calvachi, Paola; Zimetbaum, Peter; Bellows, Brandon K.; Kramer, Daniel B.; Kazi, Dhruv S.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Use of an antibiotic-eluting envelope (AEE) during cardiac implantable electronic device procedures reduces infection risk but increases procedural costs. We aim to estimate the cost-effectiveness of AEE use during cardiac implantable electronic device procedures among patients with heart failure. Methods: A state-transition cohort model of heart failure patients undergoing cardiac implantable electronic device implantation or generator replacement was developed with input parameters estimated from randomized trials, registries, surveys, and claims data. Effectiveness was estimated from the World-Wide Randomized Antibiotic Envelope Infection Prevention Trial. AEE was assumed to cost $953 per unit. The model projected mortality, quality-adjusted life-years, costs, and the incremental cost-effectiveness ratio of AEE use compared with usual care from a US healthcare sector perspective over a lifetime horizon. We assumed a cost-effectiveness threshold of $100 000 per quality-adjusted life-year gained. Results: Compared with usual care, AEE use in initial implantations produced an incremental cost-effectiveness ratio of $112 000 per quality-adjusted life-year gained (39% probability of being cost-effective). In generator replacement procedures, AEE use produced an incremental cost-effectiveness ratio of $54 000 per quality-adjusted life-year gained (84% probability of being cost-effective). Results were sensitive to the underlying rate of infection, cost of the AEE, and durability of AEE effectiveness. Conclusions: Universal AEE use for cardiac implantable electronic device procedures in patients with heart failure with reduced ejection fraction is unlikely to be cost-effective, reinforcing the need for individualized risk assessment to guide uptake of the AEE in clinical practice. Selective use in patients at increased risk of infection, such as those undergoing generator replacement procedures, is more likely to meet health system value benchmarks.